2006
DOI: 10.1191/0748233706th265oa
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate-induced renal oxidative stress in rats: the role of a novel antioxidant caffeic acid phenethyl ester

Abstract: The exact mechanisms of methotrexate-induced renal toxicity have not yet been determined. However, several hypotheses have been put forward, including oxidative stress. The aim of this study was to investigate the role of caffeic acid phenethyl ester (Caffeic Ester), a novel antioxidant, on methotrexate-induced renal oxidative stress in rats. Nineteen adult male rats were equally divided into three experimental groups as follows: control group, methotrexate-treated group, and methotrexate+Caffeic Ester-treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
68
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 34 publications
1
68
0
1
Order By: Relevance
“…It was reported that 20 mg/kg dose of Mtx, used in this study, highly exceeds interval dose and can be accepted as high dose Mtx in human (Oktem et al, 2006;Cetinkaya et al, 2007;Abdel-Raheem and Khedr, 2014). Mtx treatment at high doses may cause renal failure (Abelson et al, 1983).…”
Section: Discussionmentioning
confidence: 79%
“…It was reported that 20 mg/kg dose of Mtx, used in this study, highly exceeds interval dose and can be accepted as high dose Mtx in human (Oktem et al, 2006;Cetinkaya et al, 2007;Abdel-Raheem and Khedr, 2014). Mtx treatment at high doses may cause renal failure (Abelson et al, 1983).…”
Section: Discussionmentioning
confidence: 79%
“…In another study in Wistar albino rats, the nephrotoxic effect of MTX was associated with lipid peroxidation and reduction in antioxidant enzymatic defense capacity. 21 In this study, CAPE prevented nephrotoxicity and this effect was attributed to its scavenging activity for ROS in the kidney tissue. Therefore, we suggest that propolis prevents MTX-induced nephrotoxicity with its antioxidant properties.…”
mentioning
confidence: 62%
“…The predominant manifestation of MTX-induced lung toxicity is pulmonary fibrosis (3). In addition to pulmonary fibrosis, MTX treatment has been associated with acute interstitial pneumonitis (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%